Iklan Informatif dan Sales Promotion di Instagram: Pengaruhnya terhadap Keputusan Pembelian Skincare The Originote - Salsa Hijriyatin Nisa; Oktaviana Purnamasari (Lembaga Pengembangan Kinerja Dosen, 2025)
The purpose of this study is to examine the impact of informative advertisements and sales promotions on consumer purchase decisions, as well as to measure the partial effects of informative advertisements and sales promotions on purchase decisions, and to simultaneously assess their combined effect on consumer purchase decisions. In this study, the variable X1 represents informative advertisements, which include dimensions such as informing the market about new products, explaining how a product works, and suggesting new ways to use a product. The variable X2 represents sales promotions, which include dimensions such as coupons, price packs (money-off deals), and event marketing or event sponsorship. The variable Y in this study is consumer purchase decisions, which consist of dimensions like problem recognition, information search, alternative evaluation, purchase decision, and post-purchase behavior. This research uses a quantitative approach with a survey method and data collection through questionnaires given to 144 respondents who are followers of the Instagram account @theoriginote. The data analysis technique used is multiple linear regression, with sampling using the simple random sampling technique. The results indicate that the informative advertisement variable has an effect of 51.2%, while the sales promotion variable has an effect of 66.6%. Simultaneously, both informative advertisements and sales promotions have a combined effect of 67.9% on consumer purchase decisions, with the remaining influence coming from external factors not covered by the study.